Analyzing the forecast of tennis ball landing Points: An Interdisciplinary study of Virtual-Reality integration and Multi-Camera perspectives - Lai, Kalin Guanlun; Huang, Hsu-Chun; Lin, Shang-Yi; Lin, Wei-Ting; Lin, Kawuu Weicheng (Expert systems with applications, 2025)
Tennis virtual-reality integration represents an emerging and promising approach that combines augmented reality (AR) and mixed reality (MR) technologies to assess the flight and landing point of forecasted tennis balls across different playing fields. In this study, we utilized Multi-Camera Perspectives to analyze the forecast trajectory from both a real-world Outdoor Field and a simulated Virtual Field. Our comprehensive analysis of the results unveiled substantial distinctions in the X-axis error between the outdoor field and the virtual field. Delving deeper into the data, we conducted a meticulous decomposition of X-axis and Y-axis errors, revealing a remarkable disparity in the X-axis error for the outdoor field when compared to all other data. Our findings unequivocally demonstrate that the forecast accuracy in the outdoor field is susceptible to a myriad of disturbing factors, resulting in the pronounced X-axis error divergence. Specifically, the influence of the Magnus Effect was identified as a significant contributor to this phenomenon. Collaborative cross-disciplinary applications in sports. The implications of this study are expected to provide invaluable insights for researchers and practitioners working in the realm of sports analytics and virtual-reality applications, signifying pivotal achievements in innovative sports technology.